A dançaterapia melhora a qualidade de vida e a função neuromuscular de indivíduos com transtornos neuromotores - Machado, Lavinia Teixeira de Aguiar (2010)
The dance is a possibility of non-verbal communication. It is supposed that, like therapy, the dance can embrace and interconnect cerebral areas which are responsible for the cognition, emotion and motor action. To investigate the effect of Dance therapy as tool for improves the quality of life, ROM and functionality of subjects with neuromotor disorders. This controlled and randomized clinical trial was composed by two groups: Dance Therapy and Kinesiotherapy. Both of them were undergone to an 1-hour treatment, twice a week, along two months. The assessment instruments used were: The questionnaire about quality of Life Short-Form 36 (Brazilian version), goniometer (to ROM), and Protocol for Evaluating Motor and Functional Performance of Durigon. The applied procedures in the groups Dance therapy and Kinesiotherapy were conducted in suitable locations for their conducts. Twenty-six subjects were proportionally allocated into two groups of study. The findings suggest impairment in quality of life in various rules in both groups when analyzed through SF-36. The worst scores of quality of life were observed for the field of physical limitation in both groups (Dance Therapy 20.76±6.76, Kinesiotherapy 37.69±8.05). Significant improvement was observed for the items functional capacity (p=0.019), general health (p=0.015), social aspects (p=0.002) and limitation for emotional aspects (p=0.039) only for the group Dance Therapy after treatment. In Group Dance Therapy the sampling variances showed significant improvements in range of motion in all joints and axes of movements (p < .05). The exception was adduction movement in the shoulder joint (p=.174 and p=.082, right and left limbs, respectively). In Group Kinesiotherapy there was significant increase in the passive range of motion in some joints of the upper (p≤.015) and some joints of the lower limbs (p≤.05). A significant enhancement was observed in all of static and dynamic functional activities (p≤.04), except to anterior (p=.083) and posterior gaits (p=.157) for the Dance Therapy group. In the Kinesiotherapy group, there was a significant improvement only for sitting (p=.016) and kneeling postures (p=.025). The Dance Therapy promoted enhancement on the quality of life, the range of motion and the static and dynamic functions in patients with brain-related neuromotor disabilities.